The Role of Interleukin-6 (IL-6) in the Systemic Inflammatory Response in Xenograft Recipients and in Pig Kidney Xenograft Failure - Zhang, Guoqiang; Iwase, Hayato; Li, Qi; Yamamoto, Takayuki; Jagdale, Abhijit; Ezzelarab, Mohamed B.; Ayares, David; Cooper, David K. C.; Hara, Hidetaka; Wang, Gangcheng (Frontiers in Immunology, 2021)
Background: In pig-to-baboon transplantation models, there is increasing evidence of systemic inflammation in xenograft recipients (SIXR) associated with pig xenograft failure. We evaluated the relationship between systemic inflammatory factors and pig kidney xenograft failure. Methods: Baboons received kidney transplants from genetically engineered pigs (n=9), and received an anti-CD40mAb-based (n=4) or conventional (n=5) immunosuppressive regimen. The pig kidney grafts were monitored by measurements of serum creatinine, serum amyloid A (SAA), white blood cell (WBC) and platelet counts, plasma fibrinogen, and pro-inflammatory cytokines (baboon and pig IL-6, TNF-α, IL-1β). Results: Six baboons were euthanized or died from rejection, and 3 were euthanized for infection. Changes in serum creatinine correlated with those of SAA (r=0.56, p<0.01). Serum baboon IL-6 was increased significantly on day 1 after transplantation and at euthanasia (both p<0.05) and correlated with serum creatinine and SAA (r=0.59, p<0.001, r=0.58, p<0.01; respectively). but no difference was observed between rejection and infection. Levels of serum pig IL-6, TNF-α, IL-1β were also significantly increased on day 1 and at euthanasia, and serum pig IL-6 and IL-1β correlated with serum creatinine and SAA. The level of serum baboon IL-6 correlated with the expression of IL-6 and amyloid A in the baboon liver (r=0.92, p<0.01, r=0.79, p<0.05; respectively). Conclusion: Early upregulation of SAA and serum IL-6 may indicate the development of rejection or infection, and are associated with impaired kidney graft function. Detection and prevention of systemic inflammation may be required to prevent pig kidney xenograft failure after xenotransplantation.